PROFIT GAIN TRENDS IN MEMBER AND NON MEMBER DAIRY FARM WOMEN UNDER DAIRY COOPERATIVES - K. VENKAT RAMANA, SURESH RATHOD and (The Journal of Research, PJTSAU, 2019)
A study on the cost economics and profit gain trends in milk production of variable socio economic groups of Mulakanoor women dairy cooperative society resulted in lower average price offered for milk by cooperative compared to the other agencies in study area (Rs. 25-28 for cow milk and 30-40 for buffalo milk vs 22-28 and 30-45 rupees per litre based on fat percentage). Whereas, the overall profit gain from milk production was more in members compared to non-members. The study also established the fact that, as the herd size increased the profit was also increased. The farmers belonging to other castes have earned more profits (Rs. 66.31) compared to weaker sections (Rs. 20.64). Similar trend in profit gain of Rs. 68.51 in large family size and Rs. 121.45 in higher educational level respondents were recorded. Price paid for milk was more in non member group when compared to member group, irrespective of their socio economic variables. The labour utilization was also more in large size family group and the family labour resource utilization was efficient